2015
DOI: 10.1039/c4ra16656f
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a controlled insulin delivery system using a glucose-responsive double-layered nanogel

Abstract: Glucose-responsive glycol chitosan/sodium alginate-poly(l-glutmate-co-N-3-l-glutamylphenylboronic acid) double-layered nanogel is a promising platform for controlled insulin release systems, achieving glucose-triggered insulin release at diabetic glucose levels in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…All of the other chemicals and reagents were of analytical grade. Lys(Z) (5.00 g, 17.85 mmol) was reacted with triphosgen (2.12 g, 7.15 mmol) suspended in THF (65 mL) at 50 C for 3 h under nitrogen purging [33]. Lys(Z)-NCA was precipitated with the excess cold n-hexane and the product was purified by repeated filtration.…”
Section: Methodsmentioning
confidence: 99%
“…All of the other chemicals and reagents were of analytical grade. Lys(Z) (5.00 g, 17.85 mmol) was reacted with triphosgen (2.12 g, 7.15 mmol) suspended in THF (65 mL) at 50 C for 3 h under nitrogen purging [33]. Lys(Z)-NCA was precipitated with the excess cold n-hexane and the product was purified by repeated filtration.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, studies performed in diabetic animal models have demonstrated that NGs based on polymers functionalized with PBA derivatives can release insulin in a controlled fashion according to glucose blood levels. Actually, after administration, NGs can maintain low glucose levels for longer compared with free insulin [152,153] (Figure 9).…”
Section: Biotechnological Uses Of Nanogelsmentioning
confidence: 99%
“…Schematic picture of glucose sensitivity of a double-layered nanogel composed by glycol chitosan/sodium alginate(SA)-poly( l -glutmate- co - N -3- l -glutamylphenylboronic acid) (PGGA) encapsulating insulin and releasing it in the presence of glucose by complexation between PBA derivative and glucose. (Reprinted with permission from reference [152]. Copyright 2015 RSC).…”
Section: Figurementioning
confidence: 99%
“…The double-layered nanogel of GC/SA-PGGA was prepared by an isotropic gelation method and electrostatic interaction between GC and SA-PGGA [68]. The glucose-induced insulin release profiles at diabetic glucose levels in vitro were demonstrated.…”
Section: Glucose-triggered Drug Deliverymentioning
confidence: 99%